Is ISO 14001 certification really good to the company? a critical analysis - Reis,Aline Vomero (2018)
Abstract Paper aims This paper aims to review the literature on the ISO 14001, an international certification for manage of Environmental Management Systems through a critical analysis of the retrieved papers based on journals in three popular databases among Brazilian researchers. Originality The paper show the panorama of the ISO 14001 certification on companies presented in papers based in three databases with free access to the Brazilian academic community. Research method The present work was constructed through a critical analysis, carried out in two stages: a literature review and the discussion of the selected papers. Main findings Results showed that the benefits found by certified companies can be classified in internal, external and relations benefits. The impact of the certification on financial and organizational performances showed to be positive. Enhancement of internal processes, strengthening of results, prevention of potential problems and a larger number of stakeholders are pointed as important performance improvements. Implications for theory and practice Present the main concepts on the role of the ISO 14001 in companies, emphasizing the importance of the standard for company performance and providing a critical analysis on the standard that has been expanding in the international market.